The Relationship Between Positive Academic and Behavior Support Services: School Failure Prevention Plan - BerryTu`Jaim M.; Martin, Magy; Martin, Don (European Scientific Journal, ESJ, 2019)
Urban middle school students experience poor self-efficacy and poor attitudes toward school climates after being retained. Previous research has indicated that grade-level retention in primary and secondary education might cause long-term achievement gaps, school failure, and high school dropout rates. However, current research has yet to examine relationships between archival data retrieved on retained middle school students’ achievement outcomes and perceptions of school climate. The purpose of this nonexperimental, quantitative study was to assess the relationships between retained middle school students’ self-efficacy as measured by the School Climate Survey and their performance outcomes as measured by PowerSchool®. Bandura’s theory of self-efficacy maintains that an individual must have the belief, motivation, determination, and drive to persevere when challenged. The archival data was collected from one Northeastern urban middle school in the United States representing underachieving participants (N = 45) enrolled in the Postive Academic and Behavioral Support Program during the academic school years of 2017 and 2018. Population groups of females and males students ranged in age between 11–14 years old. A repeated measure design analyzed the same participants over 6 months by measuring archival data on achievement (grade point average [GPA]); attendance; and demographics (sex and age). Results showed significant increases in GPAs and significant increases in males’ positive perceptions of school over the school years of 2017 and 2018. The results of this study could be useful for education professionals working in urban school districts providing support services to at-risk students facing school failure.